2017
DOI: 10.1186/s12936-017-1944-3
|View full text |Cite
|
Sign up to set email alerts
|

Population-level estimates of the proportion of Plasmodium vivax blood-stage infections attributable to relapses among febrile patients attending Adama Malaria Diagnostic Centre, East Shoa Zone, Oromia, Ethiopia

Abstract: BackgroundMalaria is ranked as the leading communicable disease in Ethiopia, where Plasmodium falciparum and Plasmodium vivax are co-endemic. The incidence of P. vivax is usually considered to be less seasonal than P. falciparum. Clinical cases of symptomatic P. falciparum exhibit notable seasonal variation, driven by rainfall-dependent variation in the abundance of Anopheles mosquitoes. A similar peak of clinical cases of P. vivax is usually observed during the rainy season. However, the ability of P. vivax t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 27 publications
(33 reference statements)
11
32
0
Order By: Relevance
“…In agreement with this finding, the recent retrospective study conducted by File et al (2019) from 2013 to 2018 also confirmed the same. The present study also revealed male individuals are proportionally more affected (64%) compared to female which agrees with the report of Golassa and White (2017) , where they reported that, males are proportionally more affected by malaria in Adama City. This is due to sex related occupation in Ethiopian tradition, where males are commonly engaged in outdoor activities which when accompanied by warmer climate of the city that favors malaria transmission by increasing human vector contact ( Golassa and White, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with this finding, the recent retrospective study conducted by File et al (2019) from 2013 to 2018 also confirmed the same. The present study also revealed male individuals are proportionally more affected (64%) compared to female which agrees with the report of Golassa and White (2017) , where they reported that, males are proportionally more affected by malaria in Adama City. This is due to sex related occupation in Ethiopian tradition, where males are commonly engaged in outdoor activities which when accompanied by warmer climate of the city that favors malaria transmission by increasing human vector contact ( Golassa and White, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, variation in malaria cases as a function of frequency of respondents' previous malaria history was again found to be significantly related for the same reason. This strongly support the previous study done in Adama City in 2015 by Golassa and White (2017) , where they concluded 70% of P. vivax infections are suggested to have arisen from relapse during February to April, and 40% from August to October 2015. The epidemiological shift towards P. vivax dominance in the city could be partly due to relapse cases, the emerging trend of the parasite clone to infect Duffy negative individuals ( Mendis et al, 2001 ), and highest genetic diversity of P. vivax over P. falciparum that shows the relative evolutionary advantage of fitness to the environmental challenges.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the transmission season P. vivax cases are presumed to be arising both from new mosquito infections and relaps. [25]. The interval to relapse ranged between 80 and 105 days in this study which is longer than usual in East Asia, but is consistent with some studies from India which suggest an intermediate duration of latency [26–28].…”
Section: Discussionsupporting
confidence: 90%
“…No spatial clustering was observed for P. vivax. The loss of relatedness and household level clustering may reflect differences in the biology of these two Plasmodium species where the majority of clinical P. vivax cases are attributable to relapsing episodes and do not necessarily reflect an active circulating infection that involves www.nature.com/scientificreports/ mosquito bites 43,44 . This would contribute to considerable variation in the time between the original inoculation by mosquito bite and parasite detection in the bloodstream, and thus diffuse any genomic signal.…”
Section: Discussionmentioning
confidence: 99%